A escuta clínica no campo psi-jurídico: da queixa às demandas de reconhecimento e reparação - Costa, Natasha Maués Botelho da (2026)
This study aims to analyse the role of clinical listening in the psycho-legal field, based on the experience of psychological practice in a Law Practice Centre, considering the impasses between psychological demands and the intended juridical response. The research is justified by the growing judicialisation of daily life conflicts and the theoretical gap regarding the possibilities and limits of Clinical Psychology in this institutional context. The hypothesis is that, when called upon to respond to losses, ruptures, and psychological suffering, the law tends to operate according to a logic of imputation, producing defensive effects that hinder the recognition and elaboration of grief. This is a qualitative research of a theoretical-clinical nature, based on psychoanalytic theory, considering the Freudian-Lacanian contributions on demand, Melanie Klein’s on reparation, as well as the theory of Sándor Ferenczi accompanied by Axel Honneth and Winnicott to think about recognition. These theories were articulated with clinical vignettes and film analyses. The results indicate that institutional clinical listening, even when constrained by temporal and institutional limits, can operate as a space for symbolisation, favouring shifts from complaint to demand and enabling forms of symbolic reparation. The relevance of articulation with conflict mediation as a complementary means of transforming subjective and relational impasses is also evident